2017
DOI: 10.1093/infdis/jix273
|View full text |Cite
|
Sign up to set email alerts
|

The EVVA Cohort Study: Anal and Cervical Type-Specific Human Papillomavirus Prevalence, Persistence, and Cytologic Findings in Women Living With HIV

Abstract: Anal HPV is highly prevalent in women living with HIV, and type distribution varies by place of birth. High-resolution anoscopy was indicated in more than one third of results. As anal cancer is potentially preventable, these important findings need to be considered when selecting the best approach for anal cancer screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Similar to prior studies, we found that abnormal anal cytology is more common than abnormal cervical cytology [15]. Cambou et al screened 863 HIV-infected women and found that 30.9% had abnormal anal cytology compared with 22.4% with abnormal cervical cytology [21]. De Pokomandy et al reported that in their Canadian cohort of 151 HIV-infected women, 36.7% had abnormal anal cytology, compared with 24.3% with abnormal cervical cytology [20].…”
Section: Discussionsupporting
confidence: 88%
“…Similar to prior studies, we found that abnormal anal cytology is more common than abnormal cervical cytology [15]. Cambou et al screened 863 HIV-infected women and found that 30.9% had abnormal anal cytology compared with 22.4% with abnormal cervical cytology [21]. De Pokomandy et al reported that in their Canadian cohort of 151 HIV-infected women, 36.7% had abnormal anal cytology, compared with 24.3% with abnormal cervical cytology [20].…”
Section: Discussionsupporting
confidence: 88%
“…As chronic HPV infections in particular with multiple and high‐risk HPV represent a risk factor for AIN and anal carcinoma, subjects were clinically examined for signs of an HPV infection such as condylomata acuminata . Anal condyloma was significantly associated with abnormal screening results ( P = 0.045).…”
Section: Resultsmentioning
confidence: 99%
“…Processed cervicovaginal (n = 335) and anal (n = 75) specimens that had been collected between 2007 and 2013 from 410 participants (397 women, 13 men) in four cohort studies and one clinical trial were retrieved from processed samples stored at −80°C. [24][25][26][27][28] In each of these five studies, all participants provided written informed consent for HPV testing. Studies were approved by the local research ethics committees of participating institutions.…”
Section: Clinical Specimensmentioning
confidence: 99%